Polylactic acid fiber concrete and preparation method thereof

By introducing polylactic fibers into polypropylene fiber concrete and combining them, the problem of insufficient strength of polypropylene fiber concrete is solved, and the high compressive, flexural and flexural strength of polylactic fiber concrete is achieved, which significantly improves its performance.

CN119859042APending Publication Date: 2025-04-22ANHUI UNIV OF FINANCE & ECONOMICS +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510211316.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing polypropylene fiber concrete has shortcomings in terms of strength, which is difficult to meet the high requirements of compression, flexural resistance and bending resistance.

Method used

By using the composite technology of polylactic fiber and polypropylene fiber, a new polylactic fiber concrete is formed by adjusting the fiber content and particle size. The concrete includes cement, mineral powder, fly ash, fine aggregate, coarse aggregate, water reducer, polylactic fiber and polypropylene fiber. Through the combination of these components, the crack resistance and strength of the concrete are improved.

Benefits of technology

The compressive, flexural and flexural strength of polylactic fiber concrete has been significantly improved, with compressive strength reaching 1.15 times that of polypropylene fiber concrete, tensile initial crack strength increased by 1.13 times, and significant flexural strength increased.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005286078320000051
    Figure BDA0005286078320000051
  • Figure BDA0005286078320000081
    Figure BDA0005286078320000081
  • Figure BDA0005286078320000091
    Figure BDA0005286078320000091
Patent Text Reader

Abstract

The invention provides polylactic acid fiber concrete and a preparation method thereof, and belongs to the technical field of concrete. The polylactic acid fiber in the polylactic acid fiber concrete provided by the invention can prevent expansion of concrete cracks; when the use amount of the polypropylene fiber is not 0, the polylactic acid fiber and the polypropylene fiber are compounded for use, so that early and later cracks of the concrete can be better inhibited, a disordered support system is formed in the concrete, stress can be effectively dispersed, and expansion of the cracks can be prevented; the coal ash and the mineral powder are used for controlling synchronous development of hydration products such as C-S-H gel, and the polylactic acid fiber concrete which is good in bond stress with fibers and is microcosmically compact is formed. The compressive strength of the polylactic acid fiber concrete provided by the invention is 1.15 times that of polypropylene fiber concrete; compared with the concrete without the fiber, the tensile initial crack strength is improved by 1.13 times; and the breaking strength is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of concrete, and in particular to a polylactic acid fiber concrete and a preparation method thereof. Background Art

[0002] Concrete refers to an artificial stone obtained by uniformly mixing cement with water, sand, gravel, chemical additives and admixtures, forming and hardening it. It is easy to form, has low energy consumption and good durability, and is the most widely used building material in modern times. However, the shortcomings of concrete materials such as easy cracking, poor toughness and low tensile strength limit the application of concrete in some aspects.

[0003] Fiber concrete, also known as fiber-reinforced cement-based composite materials, is a general term for composite materials composed of fibers and cement-based materials (cement stone, mortar or concrete). By adding fibers to the cement-based materials, the tensile, bending, impact strength, elongation and toughness of the concrete can be improved. At present, the main types of fiber concrete include asbestos cement, steel fiber concrete, glass fiber concrete, polypropylene fiber concrete and carbon fiber concrete, plant fiber concrete and high elastic modulus synthetic fiber concrete. Among them, polypropylene fiber is widely used because of its advantages such as low price, easy availability and improvement of crack resistance and impermeability of concrete. However, polypropylene fiber concrete has the problem of relatively low strength.

[0004] Therefore, there is an urgent need to provide a polylactic acid fiber concrete with high compression, flexural and bending strength. Summary of the invention

[0005] The object of the present invention is to provide a polylactic acid fiber concrete with high compression, flexural and bending strength and a preparation method thereof.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The invention provides a polylactic acid fiber concrete, which comprises the following components by weight: 215-235 parts of cement, 65-85 parts of mineral powder, 75-95 parts of fly ash, 175-795 parts of water, 750-850 parts of fine aggregate, 950-1000 parts of coarse aggregate, 8-10 parts of water reducing agent, 0.45-1.2 parts of polylactic acid fiber and 0-0.9 parts of polypropylene fiber.

[0008] Preferably, the cement is silicate cement with a strength grade not less than 42.5.

[0009] Preferably, the particle size of the mineral powder is 20-25 μm.

[0010] Preferably, the particle size of the fly ash is 4-5 μm.

[0011] Preferably, the particle size of the fine aggregate is 0.2-2 mm.

[0012] Preferably, the particle size of the coarse aggregate is 5 to 25 mm.

[0013] Preferably, the water reducer is a polycarboxylate water reducer, and the polycarboxylate water reducer includes one or more of polycarboxylate ether type, polycarboxylate ester type and polycarboxylate amide type.

[0014] Preferably, the diameter of the polylactic acid fiber is 0.5 to 2 μm, and the length of the polylactic acid fiber is 8 to 10 mm.

[0015] Preferably, the diameter of the polypropylene fiber is 0.6-1.5 mm, and the length of the polypropylene fiber is 8-10 mm.

[0016] The present invention also provides a method for preparing the polylactic acid fiber concrete described in the above technical solution, comprising: mixing cement, mineral powder, fly ash, water, fine aggregate, coarse aggregate, water reducing agent, polylactic acid fiber and polypropylene fiber to obtain polylactic acid fiber concrete.

[0017] The invention provides a polylactic acid fiber concrete, which comprises the following components by weight: 215-235 parts of cement, 65-85 parts of mineral powder, 75-95 parts of fly ash, 175-795 parts of water, 750-850 parts of fine aggregate, 950-1000 parts of coarse aggregate, 8-10 parts of water reducing agent, 0.45-1.2 parts of polylactic acid fiber and 0-0.9 parts of polypropylene fiber. The cement of the present invention is used as a cementitious material to improve the strength of concrete with coarse aggregate and fine aggregate; polylactic acid fiber has good biodegradability and certain toughness, and can prevent the expansion of concrete cracks; at the same time, when the amount of polypropylene fiber is not 0, polypropylene fiber has high strength and low water absorption, and the compound use of polylactic acid fiber and polypropylene fiber can better inhibit the early and late cracks of concrete, form a random support system in concrete, and effectively disperse stress and prevent the expansion of cracks; the present invention controls the synchronous development of hydration products such as CSH gel with fly ash and mineral powder to form polylactic acid fiber concrete with good fiber grip and microscopic density. The results of the embodiment show that the compressive strength of the polylactic acid fiber concrete provided by the present invention is 1.15 times that of the polypropylene fiber concrete; compared with the concrete without fiber addition, the tensile initial crack strength is increased by 1.13 times; and the flexural strength is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a photo of the polylactic acid fiber used in Examples 1 to 4 of the present invention;

[0019] Figure 2This is a schematic diagram of the dimensions of the tensile test piece of the test example of the present invention;

[0020] Figure 3 This is a photo of the compression test equipment of the test example of the present invention;

[0021] Figure 4 It is a schematic diagram of a loading device for the flexural test of the test example of the present invention;

[0022] Figure 5 This is a photo of the on-site arrangement of the displacement meter for the flexural test of the test example of the present invention. DETAILED DESCRIPTION

[0023] The invention provides a polylactic acid fiber concrete, which comprises the following components by weight: 215-235 parts of cement, 65-85 parts of mineral powder, 75-95 parts of fly ash, 175-795 parts of water, 750-850 parts of fine aggregate, 950-1000 parts of coarse aggregate, 8-10 parts of water reducing agent, 0.45-1.2 parts of polylactic acid fiber and 0-0.9 parts of polypropylene fiber.

[0024] In the present invention, unless otherwise specified, the raw materials used in the present invention are all commercially available products well known to those skilled in the art.

[0025] The polylactic acid fiber concrete provided by the present invention includes 215 to 235 parts of cement, preferably 225 to 230 parts. In the present invention, the cement is preferably a silicate cement with a strength grade not less than 42.5. In the present invention, the silicate cement with a strength grade not less than 42.5 as a cementitious material mainly plays the role of wrapping aggregates and making the polylactic acid fiber concrete have higher strength.

[0026] Based on 215 to 235 parts by weight of cement, the polylactic acid fiber concrete provided by the present invention includes 65 to 85 parts of mineral powder, preferably 70 to 75 parts. In the present invention, the source of the mineral powder is preferably granulated blast furnace slag. The present invention has no special restrictions on the source of the granulated blast furnace slag, and conventional granulated blast furnace slag can be used. The use of mineral powder in the present invention can improve the workability, strength and durability of polylactic acid fiber concrete, reduce production costs, and has good environmental benefits.

[0027] In the present invention, the particle size of the mineral powder is preferably 20 to 25 μm. The present invention controls the particle size of the mineral powder within the above range, which can improve the fluidity of the polylactic acid fiber concrete.

[0028] The polylactic acid fiber concrete provided by the present invention includes 75 to 95 parts of fly ash, preferably 80 to 85 parts, based on 215 to 235 parts by weight of cement. In the present invention, the particle size of the fly ash is preferably 4 to 5 μm. In the present invention, the fly ash can save cement and fine aggregate, reduce water consumption, and improve the workability of the concrete mixture.

[0029] Based on 215 to 235 parts by weight of cement, the polylactic acid fiber concrete provided by the present invention includes 175 to 795 parts of water, preferably 180 to 185 parts. In the present invention, the water is used as a dispersion medium of the polylactic acid fiber concrete.

[0030] Based on 215 to 235 parts by weight of cement, the polylactic acid fiber concrete provided by the present invention includes 750 to 850 parts of fine aggregate, preferably 800 to 820 parts. In the present invention, the fine aggregate is preferably natural sand. In the present invention, the particle size of the fine aggregate is preferably 0.2 to 2 mm, more preferably 1 to 2 mm; the fineness modulus of the fine aggregate is preferably 2.3 to 3.1, and the packing density of the fine aggregate is preferably 1450 to 1550 kg / m 3 , more preferably 1500-1550 kg / m 3 The present invention utilizes fine aggregate to play a role of skeleton or filling in concrete.

[0031] Based on 215 to 235 parts by weight of cement, the polylactic acid fiber concrete provided by the present invention includes 950 to 1000 parts of coarse aggregate, preferably 800 parts. In the present invention, the coarse aggregate is preferably graded crushed stone. In the present invention, the particle size of the coarse aggregate is preferably 5 to 25 mm, more preferably 10 to 20 mm; the fineness modulus of the coarse aggregate is preferably 3.7 to 4.7, and the bulk density of the coarse aggregate is preferably 1500 to 1600 kg / m 3 The present invention utilizes coarse aggregate to play a role of skeleton or filling in concrete.

[0032] The present invention adopts fine aggregate and coarse aggregate at the same time, adopts different particle size gradations, and together plays a role of skeleton or filling in the polylactic acid fiber concrete, which can improve the strength of the polylactic acid fiber concrete.

[0033] Based on 215 to 235 parts by weight of cement, the polylactic acid fiber concrete provided by the present invention includes 8 to 10 parts of a water reducer, preferably 9 to 10 parts. In the present invention, the water reducer is preferably a polycarboxylic acid water reducer, and the polycarboxylic acid water reducer preferably includes one or more of a polycarboxylic acid ether type, a polycarboxylic acid ester type, and a polycarboxylic acid amide type. The present invention utilizes a water reducer to reduce water consumption, thereby improving the compactness and hardness of the polylactic acid fiber concrete and increasing its fluidity.

[0034] Based on 215 to 235 parts by weight of cement, the polylactic acid fiber concrete provided by the present invention includes 0.45 to 1.2 parts of polylactic acid fiber. In an embodiment of the present invention, the weight proportion of the polylactic acid fiber may be 0.45, 0.6, 0.9 or 1.2 parts. In the present invention, the diameter of the polylactic acid fiber is preferably 0.5 to 2 μm, more preferably 0.9 to 1.5 μm; the length of the polylactic acid fiber is preferably 8 to 10 mm, more preferably 9 to 10 mm. The polylactic acid fiber used in the present invention can prevent the expansion of concrete cracks and improve the strength and toughness of polylactic acid fiber concrete. In an embodiment of the present invention, the source of the polylactic acid fiber may be high-strength fine-denier polylactic acid short fibers produced by Anhui Fengyuan Biofiber Co., Ltd.

[0035] Based on 215 to 235 parts by weight of cement, the polylactic acid fiber concrete provided by the present invention includes 0 to 0.9 parts of polypropylene fibers. In an embodiment of the present invention, the weight percentage of the polypropylene fibers may be 0, 0.45 or 0.9. In the present invention, the diameter of the polypropylene fibers is preferably 0.6 to 1.5 mm, more preferably 0.9 to 1.2 mm; the length of the polypropylene fibers is preferably 8 to 10 mm, more preferably 9 to 10 mm. The polypropylene fibers used in the present invention can prevent the expansion of concrete cracks, and the polypropylene fibers have high strength and low water absorption. The compound use of polylactic acid fibers and polypropylene fibers can better inhibit early and late cracks in concrete, form a random support system in concrete, effectively disperse stress, prevent the expansion of cracks, and improve the strength and toughness of polylactic acid fiber concrete.

[0036] The present invention also provides a method for preparing the polylactic acid fiber concrete described in the above technical solution, comprising: mixing cement, mineral powder, fly ash, water, fine aggregate, coarse aggregate, water reducing agent, polylactic acid fiber and polypropylene fiber to obtain polylactic acid fiber concrete.

[0037] The present invention has no particular limitation on the method of mixing the cement, mineral powder, fly ash, water, fine aggregate, coarse aggregate, water reducing agent, polylactic acid fiber and polypropylene fiber, as long as the components are fully mixed. In an embodiment of the present invention, the mixing method may be stirring.

[0038] The cement of the present invention is used as a cementitious material, and the coarse aggregate and the fine aggregate are used to improve the strength of the concrete. The lactic acid fiber and the polypropylene fiber are used in combination, which can better inhibit the early and late cracks of the concrete, form a random support system in the concrete, and can effectively disperse the stress and prevent the expansion of the cracks. The present invention uses fly ash and mineral powder to control the synchronous development of hydration products such as CSH gel, and forms a polylactic acid fiber concrete with good fiber bond strength and microscopic density, so that the strength of the polylactic acid fiber concrete after hardening is significantly improved.

[0039] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Raw materials and sources used in the examples of the present invention:

[0041] Cement: Ordinary Portland Cement P·O42.5, sourced from Anhui Pearl Cement Group Co., Ltd.;

[0042] Mineral powder: particle size is 20-25 μm, sourced from Chuzhou Wanjuan New Materials Co., Ltd.

[0043] Fly ash: particle size is 4-5 μm, sourced from Anhui Guiyuan Co., Ltd.;

[0044] Fine aggregate: particle size is 0.2-2mm, sourced from Anhui Qiangli New Material Technology Co., Ltd.;

[0045] Coarse aggregate: particle size is 5-25mm, sourced from Anhui Qiangli New Material Technology Co., Ltd.;

[0046] The water reducer is: polycarboxylate water reducer, sourced from Nantong Runfeng Petrochemical Co., Ltd.;

[0047] Polylactic acid fiber (PLA fiber): such as Figure 1 As shown; the average diameter is 1.5μm, and the source is the high-strength fine-denier polylactic acid staple fiber produced by Anhui Fengyuan Biofiber Co., Ltd.;

[0048] Polypropylene fiber (PP fiber): diameter 0.9 mm, sourced from Guangxi Huayi New Materials Co., Ltd.;

[0049] Among them, the performance parameters of polylactic acid fiber and polypropylene fiber are shown in Table 1:

[0050] Table 1 Performance parameters of polylactic acid fiber and polypropylene fiber

[0051]

[0052] In the embodiment, a forced mixer is used to mix the materials uniformly to obtain polylactic acid fiber concrete. In the comparative example, a forced mixer is used to mix the materials uniformly to obtain fiber concrete.

[0053] Example 1

[0054] A polylactic acid fiber concrete comprises, by weight, 225 parts of cement, 75 parts of mineral powder, 85 parts of fly ash, 185 parts of water, 800 parts of fine aggregate, 980 parts of coarse aggregate, 9 parts of water reducing agent, 0.6 parts of PLA fiber and 0 parts of polypropylene fiber.

[0055] Example 2

[0056] A polylactic acid fiber concrete comprises, by weight, 225 parts of cement, 75 parts of mineral powder, 85 parts of fly ash, 185 parts of water, 800 parts of fine aggregate, 980 parts of coarse aggregate, 9 parts of water reducing agent, 0.9 parts of PLA fiber and 0 parts of polypropylene fiber.

[0057] Example 3

[0058] A polylactic acid fiber concrete comprises the following components by weight: 225 parts of cement, 75 parts of mineral powder, 85 parts of fly ash, 185 parts of water, 800 parts of fine aggregate, 980 parts of coarse aggregate, 9 parts of water reducing agent, 1.2 parts of PLA fiber and 0 part of polypropylene fiber.

[0059] Example 4

[0060] A polylactic acid fiber concrete comprises, by weight, 225 parts of cement, 75 parts of mineral powder, 85 parts of fly ash, 185 parts of water, 800 parts of fine aggregate, 980 parts of coarse aggregate, 9 parts of water reducing agent, 0.45 parts of PLA fiber and 0.45 parts of polypropylene fiber.

[0061] Comparative Example 1

[0062] A concrete comprises, by weight, 225 parts of cement, 75 parts of mineral powder, 85 parts of fly ash, 185 parts of water, 800 parts of fine aggregate, 980 parts of coarse aggregate and 9 parts of water reducing agent.

[0063] Comparative Example 2

[0064] A concrete comprises, by weight, 225 parts of cement, 75 parts of mineral powder, 85 parts of fly ash, 185 parts of water, 800 parts of fine aggregate, 980 parts of coarse aggregate, 9 parts of water reducing agent, 0 parts of PLA fiber and 0.9 parts of polypropylene fiber.

[0065] Test Example 1

[0066] The polylactic acid fiber concrete prepared in Examples 1 to 4 and the concrete prepared in Comparative Examples 1 to 2 were poured into the molds respectively, vibrated on a vibration table, and demolded after 24 hours of pouring. After demolding, the concrete was placed in a standard curing room (the temperature was constant at 20°C ± 2°C, and the humidity was not less than 95%) for curing. The properties of the specimens were tested when the curing age was 28 days. Then, the specimens to be tested were prepared, with 3 groups for each specimen. The size of the compressive specimen was a 150mm×150mm×150mm cube, the size of the flexural specimen was a 100mm×100mm×400mm cuboid, and the size of the tensile specimen was Figure 2 The unit is mm. With reference to the Standard Test Methods for Physical and Mechanical Properties of Concrete (GB / T50081-2019), the Standard Test Methods for Fiber Concrete (CECS13-2009) and the Standard Test Method for Flexural Toughness and First-Crack Strength of Fiber-Reinforced Concrete (ASTM C1018), tensile strength tests, compressive strength tests and flexural strength tests were carried out. Mechanical properties tests of cube compressive strength, axial tensile strength and flexural strength were carried out on a 2000kN microcomputer-controlled electro-hydraulic servo pressure testing machine. The test force data was collected using the load sensor provided by the press, and the strain and displacement data of the specimens were collected using the TDS-540 data acquisition instrument.

[0067] Compression test equipment photo Figure 3 As shown: Referring to the Standard for Test Methods for Physical and Mechanical Properties of Concrete (GB / T50081-2019), the compressive strength of concrete cube specimens was determined. The loading device of this test adopted a 10t microcomputer-controlled universal testing machine. The side of the specimen when it was formed was used as the pressure-bearing surface. The specimen was placed on the lower pressure plate of the testing machine. The center of the specimen was aligned with the center of the lower pressure plate of the testing machine. The test process was recorded continuously and evenly. The loading speed was 0.5MPa·s -1 The compressive strength of concrete cube specimen is calculated according to the following formula I:

[0068] F cc =F / A Formula I;

[0069] In Formula I: F cc is the compressive strength of the concrete cube specimen (MPa); F is the specimen failure load (N); A is the specimen pressure bearing area (mm 2 ).

[0070] Tensile test: refer to the "Fiber Concrete Test Method Standard" (CECS13-2009), determine the axial tensile strength of fiber concrete specimens, axial tensile stress-strain curve, the loading device of this test uses a 10t microcomputer-controlled universal testing machine, the tensile stress-strain curve of the material is tested by a dumbbell-shaped specimen, the cross-sectional area of ​​the middle test section of the specimen is small, to ensure that the middle test section reaches the tensile strength limit value first during the test. The two ends of the 100mm standard test section of the specimen are fixed by a clamp, and a resistance strain gauge is pasted on the 100mm standard test section as a micro-deformation measuring instrument. The test data is collected by the automatic data acquisition system. The specimen is continuously and evenly loaded. The loading speed before the maximum load is 0.4MPa / min, and then it is controlled by deformation and taken at 0.1~0.2mm / min. When the specimen is close to failure and the deformation speed increases, the throttle of the testing machine should be stopped until the specimen is destroyed. Record the maximum load, accurate to 0.1MPa. The axial tensile strength of concrete is calculated according to the following formula II:

[0071] F fc,t =F tmax / A Formula II;

[0072] In formula II: F fc,t is the axial tensile strength of fiber concrete (MPa); F tmax is the specimen failure load (N); A is the cross-sectional area of ​​the specimen (mm 2 ).

[0073] Flexural test: The schematic diagram of the loading device for the flexural test is as follows Figure 4 The on-site photos of the displacement gauge arrangement for the flexural test are shown in Figure 5As shown. With reference to the "Fiber Concrete Test Method Standard" (CECS13-2009), the initial crack strength and load-deflection curve of the fiber concrete specimen when bent were determined. The loading device of this test uses a 10t microcomputer-controlled universal testing machine. When the fiber length is not more than 40mm, a beam specimen with a cross-section of 100mm×100mm is used. The flexural test of the rectangular test block of 100mm×100mm×400mm is carried out. The support spacing is set to 3 times the side length of the cross section according to the specification requirements, that is, the support spacing is 300mm. The distribution beam is loaded. The testing machine is equipped with it or after assembly. The midpoint of the distribution beam is equipped with a roller shaft. Two pressurized universal roller shafts are set at the three-point point of the specimen gauge length. The roller shaft can roll and tilt freely forward and backward (perpendicular to the axis direction of the specimen). The roller shaft diameter is 30mm. The two roller bearings in contact with the specimen have an arc diameter of 30mm and a bearing length 10mm longer than the width of the specimen. One of the bearings is a fixed hinge and the other is a universal rolling hinge. The bearing can roll and tilt freely forward and backward (perpendicular to the axis of the specimen). Load-deflection curve, deflection measurement uses an LVDT displacement meter with a range of not less than 5mm and an accuracy of not less than 0.001mm. The load tester can use the load test system of the testing machine. After the specimen is placed, slowly load it to 1kN, stop the machine to check the contact between the specimen and the pressure head and the bearing to ensure that the specimen does not twist, and then install the instrument to measure the mid-span deflection. The loading rate before the initial crack is 0.05~0.08MPa / s, and displacement control can be used. After the initial crack, displacement control is used, and the rate is per minute to make the deflection growth rate the same. Draw a load-deflection curve. The flexural strength of concrete is calculated according to the following formula III:

[0074] f cr =F cr L / bh 2 Formula III;

[0075] In formula III, f cr F is the initial flexural strength of fiber reinforced concrete (MPa); cr is the initial crack load of fiber concrete (N); L is the span between the test beam supports (mm); b is the section width (mm); and h is the section height (mm).

[0076] The compressive strength test results are shown in Table 2:

[0077] Table 2 Compressive strength test results of different samples

[0078]

[0079]

[0080] In Table 2, CC, C-PLA06-FRC, C-PLA09-FRC, C-PLA12-FRC, C-PP09-FRC and C-PP045-FRC045 respectively refer to the samples prepared in Comparative Example 1, Example 1, Example 2, Example 3, Comparative Example 2 and Example 4.

[0081] As can be seen from Table 2, the compressive strength found that with the increase of PLA fiber content, the compressive strength of PLA fiber concrete did not change much; compared with ordinary concrete, PLA fiber concrete did not show obvious cracks when it was destroyed, and no concrete shedding occurred; at the same fiber content, the compressive strength of PLA fiber concrete was 1.15 times that of PP fiber concrete; the concrete strength of mixed PP fiber and PLA fiber was the largest, and the fiber distribution uniformity of mixed fiber concrete was high.

[0082] The tensile strength test results are shown in Table 3:

[0083] Table 3 Tensile strength test results of different samples

[0084]

[0085]

[0086] In Table 3, TC, T-PLA06-FRC, T-PLA09-FRC, T-PLA12-FRC, T-PP09-FRC and T-PP045-FRC045 refer to the samples prepared in Comparative Example 1, Example 1, Example 2, Example 3, Comparative Example 2 and Example 4, respectively.

[0087] The tensile test found that more microcracks developed during the destruction process. Unlike the sudden brittle failure of ordinary concrete, fiber concrete showed certain ductile failure characteristics; with the increase of PLA fiber content, the tensile strength of PLA fiber concrete first increased and then decreased; the tensile strength of PLA-FRC with a fiber content of 0.9 parts was the largest; compared with ordinary concrete, the tensile initial crack strength of PLA fiber concrete increased by 1.13 times.

[0088] The flexural strength test results are shown in Table 4:

[0089] Table 4 Flexural strength test results of different samples

[0090]

[0091]

[0092] In Table 4, FC, F-PLA06-FRC, F-PLA09-FRC, F-PLA12-FRC, F-PP09-FRC and F-PP045-FRC045 respectively refer to the samples prepared in Comparative Example 1, Example 1, Example 2, Example 3, Comparative Example 2 and Example 4. It can be seen from Table 4 that the flexural strength of PLA fiber concrete is related to the PLA fiber content; the flexural initial crack strength of PLA fiber concrete increases first and then decreases with the increase of PLA fiber content.

[0093] From the above results, it can be seen that the strain hardening and strength of fiber-reinforced concrete materials during loading vary with the type of fiber doping; the reinforcement effect of concrete materials with single PLA fiber doping is better than that of concrete materials with single PP fiber doping, PLA-FRC has high flexural strength and better elongation than PPFRC; the hybrid fiber-reinforced concrete material PLA-PP-FRC has high flexural strength, which is better than PLA-FRC and PP-FRC.

[0094] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A polylactic acid fiber concrete, comprising the following components by weight: 215-235 parts of cement, 65-85 parts of mineral powder, 75-95 parts of fly ash, 175-795 parts of water, 750-850 parts of fine aggregate, 950-1000 parts of coarse aggregate, 8-10 parts of water reducing agent, 0.45-1.2 parts of polylactic acid fiber and 0-0.9 part of polypropylene fiber.

2. The polylactic acid fiber concrete according to claim 1, characterized in that: The cement is silicate cement with a strength grade not less than 42.

5.

3. The polylactic acid fiber concrete according to claim 1, characterized in that: The particle size of the mineral powder is 20-25 μm.

4. The polylactic acid fiber concrete according to claim 1, characterized in that: The particle size of the fly ash is 4-5 μm.

5. The polylactic acid fiber concrete according to claim 1, characterized in that: The particle size of the fine aggregate is 0.2 to 2 mm.

6. The polylactic acid fiber concrete according to claim 1, characterized in that: The particle size of the coarse aggregate is 5 to 25 mm.

7. The polylactic acid fiber concrete according to claim 1, characterized in that: The water reducer is a polycarboxylic acid water reducer, and the polycarboxylic acid water reducer includes one or more of a polycarboxylic acid ether type, a polycarboxylic acid ester type and a polycarboxylic acid amide type.

8. The polylactic acid fiber concrete according to claim 1, characterized in that: The diameter of the polylactic acid fiber is 0.5 to 2 μm, and the length of the polylactic acid fiber is 8 to 10 mm.

9. The polylactic acid fiber concrete according to claim 1, characterized in that: The diameter of the polypropylene fiber is 0.6-1.5 mm, and the length of the polypropylene fiber is 8-10 mm.

10. The method for preparing the polylactic acid fiber concrete according to any one of claims 1 to 9, comprising: The polylactic acid fiber concrete is obtained by mixing cement, mineral powder, fly ash, water, fine aggregate, coarse aggregate, water reducing agent, polylactic acid fiber and polypropylene fiber.